Estudio comparativo de colorantes naturales y sintéticos de sustratos tipo clorofila utilizados en la sensibilización del TiO2 para procesos fotocatalíticos (2020)
Solar energy is an inexhaustible source and approaches to capture and exploit the sun’s energy could provide benefits beyond any expectation. Numerous studies have focused on chlorophyll as a sensitizer in photocatalytic process applications that seek to use the energy of the sun efficiently. This degree work makes a comparison between chlorophyll type sensitizers of natural origin and synthetic origin, by identifying the determining parameters of the sensitizer and the differences between the methods of obtaining and comparison of the photocatalytic activities that both types of dyes present. The application of dyes in the development of these technologies is promising, since satisfactory efficiencies have been achieved in recent years in both synthetic and natural dyes.